Protein profile analysis of two australian snake venoms by one-dimensional gel electrophoresis and MS/MS experiments - Georgieva, Dessislava; Hildebrand, Diana; Simas, Rodrigo; Coronado, Monika A. [UNESP]; Kwiatkowski, Marcel; Schlüter, Hartmut; Arni, Raghuvir [UNESP]; Spencer, Patrick; Betzel, Christian (Bentham Science Publishers, 2017)
The Pseudechis colletti and Pseudechis butleri venoms were analyzed by 1-D gel electrophoresis, followed by mass spectrometric analysis of tryptic peptides obtained from the protein bands. Both venoms contain highly potent pharmacologically active components, which were assigned to the following protein families: basic and acidic phospholipases A2 (PLA2s), L-amino acid oxidases (LAAOs), P-III metalloproteinases (P-III SVMPs), 5’-nucleotidases (5’-NTDs), cysteine-rich secretory proteins (CRISPs), venom nerve growth factors (VNGFs) and post-synaptic neurotoxins. Considerable predominance of PLA2s over other toxins is a characteristic feature of both venoms. The major differences in the venom compositions are the higher concentration of SVMPs and CRISPs in the P. butleri venom, as well as the presence of post-synaptic neurotoxins. Furthermore, the analysis revealed a high concentration of proteins with myotoxic, coagulopathic and apoptotic activities. PLA2s are responsible for the myotoxic and anticoagulant effects observed in patients after envenomation (4). The other protein families, encountered in the two venoms, probably contribute to the major symptoms described for these venoms. These results explain the observed clinical effects of the black snake envenomation. The analyzed venoms contain group P-III metalloproteinases of medical importance with the potency to be used for diagnostic purposes of von Willebrand factor (vWF) disease, for regulation of vWF in thrombosis and haemostasis, for studying the function of the complement system in host defense and in the pathogenesis of diseases. Comparison of venomic data showed similarities in the major venom components of snakes from the genus Pseudechis, resulting in common clinical effects of envenomation, and demonstrating close relationships between venom toxins of Elapidae snakes.
Keywords: Protein profile analysis; Proteome; Pseudechis butleri; Pseudechis colletti; Snake venom